Water-Mediated Three-Component Wittig–SNAr Reactions - Xu, Zian; Zhai, Wanwan; Feng, Congpeng; Liu, Hongwei; Zhao, Jianhong; Yu, Xinhong (Synlett, 2015)
A novel one-pot, three-component Wittig–SNAr approach to ethyl (E)-3-[4-(morpholino-1-yl)-3-nitrophenyl]acrylate, ethyl (E)-3-[3-cyano-4-(morpholino-1-yl)phenyl]acrylates, ethyl (E)-3-[2-(morpholino-1-yl)-5-nitrophenyl]acrylate, ethyl (E)-3-[5-(morpholino-1-yl)-4-nirtofuryl-2-yl]acrylates, and their analogues, which would be used as intermediates of aurora 2 kinase inhibitors ,etc. has been developed starting from readily available nitro- or cyano-group-activated haloaromatic aldehydes, secondary amines, quaternary phosphonium salts, and sodium hydroxide, using water as a solvent, with high stereoselectivity and in moderate to high yield. The noteworthy features of this one-pot, three-component process is highlighted by its rapid and highly efficient formation of a new C(sp2)–N bond and a new C(sp2)–C(sp2) double bond using water as a simple nontoxic convenient and environmentally benign solvent under metal-free mild reaction conditions.
Keywords: three-component reaction; Wittig reaction; SNAr; water